Income potential index analysis of hungarian cities and towns - Áldorfainé Czabadai, Lilla; Topa, Zoltán; Áldorfai, György (Studia Mundi – Economica, 2017)
It is crucial to learn which factors could influence the income status of a region. In our study we try to collect basic data which well-represent the chosen topic, and more importantly, which are easy to access and are interpretable on smaller (for example settlement) territorial levels. Based on our hypothesis the received subsidies, the taxes paid by local people and the gross value added generated by local enterprises show strong correlation with the formation of the income status, and this hypothesis was tested for cities and towns in this paper.
Keywords: income; gross value added; subsidy; development